119 THE INCREASED USAGE OF HUMIDIFIED HIGH-FLOW NASAL CANNULA VERSUS NASAL CONTINUOUS POSITIVE AIRWAY PRESSURE FOR NEONATAL RESPIRATORY DISEASE: OBSERVATIONS AND A RETROSPECTIVE STUDY. (1st January 2006) - Shoemaker, M. T.; Powers, G. C.; Pierce, M.; DiGeronimo, R. J.
Abstract : The use of humidified high-flow nasal cannula (HFNC) has expanded greatly in the last several years despite any published trials regarding its safety and/or efficacy in neonates, essentially becoming the treatment of choice over nasal CPAP (NCPAP) in many centers. Objective: To describe the prevalence of usage of HFNC vs NCPAP in two large tertiary care hospitals in neonates admitted with respiratory disease. Methods: Data were retrospectively reviewed for all NICU admissions from both Wilford Hall MC and Santa Rosa Children's Hospital during the study period. June 2004 was identified as a time point in both centers when the use of HFNC became readily available. Given this, data were collected for those admissions occurring 11 months prior to June 2004 (Era 1) and compared to those admissions occurring 11 months after (Era 2). Subgroup analysis was additionally done for VLBW (defined as < 30 weeks' gestation). This study was independently approved by the IRB of both institutions. Results: The use of NCPAP in Era 2 vs Era 1 decreased remarkably from 15% to 2.5% for all NICU admissions and from 39% to 6.7% in VLBW infants. During this same period, the use of HFNC increased from 14% to 61% overall and from 39% to 97% in VLBW infants. In Era 1, there were 566 total admissions and 72 for VLBW infants, compared to 597 and 89 admissions, respectively, for Era 2. Mortality rate (4.0% vs 3.6%) and mean ventilator days (4.0 vs 3.0) overall were similar between the two eras. In VLBW infants, mortality rate decreased from 12.5% to 8.9% and mean ventilator days decreased from 16.2 6 SD to 11.2 6 SD days in Era 1 vs Era 2, respectively. Similar complication rates to include nosocomial infections were found in both eras. Conclusions: In our study, the use of HFNC has largely replaced NCPAP for the routine treatment of neonatal respiratory disease and is almost universally used in VLBW infants. HFNC therapy additionally appears to be as efficacious and safe as NCPAP therapy. Further analysis needs to be done to determine whether HFNC improves neonatal outcomes.